Politik Organisasi dalam Latar Sumber-Sumber Kekuasaan di Lingkungan Kerja - Audah, Ali; Saragih, Sahat (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
Research aim to enhancement of understanding of perception oforganizational politics from power sources perspective. Research subject are 51employees from various work organization. Perception of organizational politicsmeasured with researcher design scale. Power sources measured with standardizedscale. Data analyzed with multiple regression. Result of analysis shows: 1) F = 2,637and p = 0,046 (p < 0,05), legitimate power, reward power, expert power and referentpower simultaneously are in the same direction correlate with perception oforganizational politics with contribution of 18,7%; 2) Legitimate power B = – 0,340and p = 0,059 (p > 0,05) partially uncorrelated with perception of organizationalpolitics; 3) Reward power B = 1,601 and p = 0,046 (p < 0,05) shows that withcontrolling of legitimate, expert, and referent power, then correlation between rewardpower with perception of organizational politics significantly is in the same direction;4) Expert power B = – 0,649 and p = 0,277 (p > 0,05) partially uncorrelated withperception of organizational politics, and 5) Referent power B = – 1,304 and p =0,030 (p < 0,05) partially negative correlated with perception of organizationalpolitics.Keywords : organizational politics, legitimate power, reward power, expert powerreferent power